Efficacy of Nano-Encapsulated Citronella Essential Oil Against Anthracnose on Bird’s Eye Chili (Colletotrichum spp.) - Dian Utami; Danar Wicaksono (Universitas Wiralodra, 2026)
Anthracnose caused by Colletotrichum spp. leads to significant losses in bird’s eye chili (Capsicum frutescens L.) production, including reduced fruit quality, lower yield, and increased production costs. Although synthetic pesticides are widely used for disease management, their prolonged application raises concerns regarding environmental sustainability and food safety. This study aimed to evaluate the antifungal potential of citronella essential oil, in both free and nano-encapsulated forms, against Colletotrichum spp. Compared to the previous studies, this work uniquely evaluates and compares nano-encapsulated and non-encapsulated citronella essential oil against anthracnose in bird’s eye chili. The experiment was arranged in a Completely Randomized Design (CRD) with treatments consisting of citronella essential oil at concentrations of 0.125% and 0.063%, either encapsulated or non-encapsulated, tested under in vivo and in vitro conditions. Parameters observed were incubation period, disease intensity, inhibition percentage, colony appearance, and hyphal morphology. Data were analyzed using ANOVA at a 5% significance level, followed by Duncan’s Multiple Range Test (DMRT) when significant differences were detected. Application of 0.125% citronella essential oil effectively delayed incubation (6.05 DAI), resulting in a disease intensity of 45%, and achieved the highest in vitro inhibition (92.21%) until 10 DAI, outperforming Propineb 70 WP and other treatments. Colony morphology remained generally similar, but notable differences in hyphal fate were observed, including lysis, shrinkage, curling, and unbranched growth. These findings indicate that citronella essential oil is a promising natural candidate to reduce reliance on Propineb 70 WP. However, further field-scale evaluations are needed.